Solo urbano, solo não urbano e solo rural: classificações do solo pelo critério da funcionalidade - Seifert, Ronaldo Gerd (2008)
This work s first objective is to present two proposals of soil classification based on the legal system s property rights. In the first proposal, a differentiation between urban soil and rural soil will be made; in the second, the same will be done between urban soil and non-urban soil. A farther objective is to use this classification, through its uses, to induce the judicial operators to its conclusions related to the application of the law regarding real estate. Doctrine classifies the soil in urban and rural based on many perspectives and ends. Therefore, there are different classifications of the same gender in species with the same nomenclature. Classifications of the soil in urban and rural can be made based on its destiny, based on the localization, and based on fiscal criteria. This work justifies itself by the fact that none of its classifications differentiates the urban and rural soil from the perspective of the rights and duties of the proprietor. None of them has the goal of finding out in which properties it is possible to have urban activities and rural activities. Besides, since not all soil that isn t urban can have a rural use, it is important to classify the soil in urban and non-urban. The delimitation that the city makes of its urban perimeter is not enough to add to the right of property, faculties related to urban activity. The essential element for the alteration of the functionality of the real estate is the urbanization of the area. As for the methodology, the rational deductive method was used, with its normative foundation being the Federal Constitution and general norms. In this way, respecting the constitutional supplemental competencies, the work includes the soil of all national territory. The final result was that two soil classification proposals were presented: urban soil and non-urban soil and; urban soil and rural soil